Larangan Riba dalam QS. Al-Baqarah 275–276: Studi Komparatif Tafsir Al-Qurthubi (Klasik-Fiqhi) dan Tafsir Al-Mishbah (Kontemporer-Kontekstual) - Februari, Budi; Nurhayati; Yenni Samri Juliati Nasution (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2025)
This study examines how the Tafsir Al-Qurtubi and Tafsir Al-Mishbah interpret Surah Al-Baqarah verses 275–276 and their implications for understanding riba (usury) in the context of modern society. This study begins with the following main questions: How do the two commentators interpret the verse, what are the differences in their approaches, and how do these differences contribute to explaining riba in the contemporary era? The method used is qualitative research based on literature review, examining primary sources in the form of two tafsir books and other supporting literature. The results show that both agree on the absolute prohibition of riba, but differ in their emphasis: Al-Qurtubi uses a textual fiqh approach, while Al-Mishbah prioritizes the social context and values ​​of justice. These differences in approach enhance understanding that the prohibition of riba is not only normative legal but also related to ethics, justice, and protecting modern society from exploitative economic practices.